Effects of supplementation with vitamin D3 on growth performance, lipid metabolism and cecal microbiota in broiler chickens - Li, Jiawei; Li, Ximei; Tian, Jiamin; Xu, Linna; Chen, Yan; Jiang, Susu; Zhang, Guohua; Lu, Jianxiong (Frontiers in Veterinary Science, 2025)
Lower intramuscular fat (IMF) and excessive abdominal fat reduce carcass quality in broilers. The study aimed to investigate the effects of dietary VD3 on growth performance, lipid metabolism and cecal microbiota in broilers over an 84-d feeding experiment. One-day-old male Luhua broilers (210) were randomly assigned to control (basal diet) and VD group (basal diet supplemented with 3,750 IU/kg VD3). Samples were collected after a 12-h fasted feeding on days 28, 56, and 84. Supplementary VD3 significantly enhanced average daily gain (ADG) in broilers aged 57-84 d and 1-84 d, and increased leg muscle rate and fat content in breast and leg muscles and reduced abdominal fat rate of broilers at 84 d. VD3 increased TG and glycogen content in the liver of 28- and 84-d-old broilers, serum TG and VLDL-C content at 56 and 84 d, and TC, HDL-C and LDL-C at 84 d. VD3 increased mRNA expressions of genes related to de novo lipogenesis (DNL) (mTOR, SREBP-1c, FAS and ACC), lipid oxidation (AMPK, PPARα, CPT-1α and ACO) and lipid transport (ApoB and MTTP), and FAS, ACC and CPT1 enzyme activities in the liver. However, mRNA levels of genes involved in DNL and cellular lipid uptake (LPL and FATP1) and LPL activity were decreased in abdominal adipose tissue, and that of genes involved in lipid oxidation and lipolysis (HSL and ATGL) was increased by VD3. LPL and FATP1 expression in breast and leg muscles was increased by VD3. Moreover, VD3 increased the abundance of cecum Bacteroides at 28 and 84 d, Rikenellaceae_RC9_gut_group and Faecalibacterium at 56 and 84 d, and Lachnoclostridium at 84 d. These bacteria were correlated with increased DNL, lipid oxidation and lipid transport in liver, and cellular lipid uptake in muscle, as well as decreased DNL and cellular lipid uptake, and increased lipid oxidation and lipolysis in abdominal adipose tissue. Altogether, supplementary VD3 in basal diet improved growth performance, increased IMF, and reduced abdominal fat rate, which is significant for enhancing feed utilization and improving the carcass quality of broilers. The regulation of VD3 on lipid metabolism could was associated with variation in cecal microbiota composition.